2018
DOI: 10.3389/fpls.2018.01683
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Locus Genome-Wide Association Studies for 14 Main Agronomic Traits in Barley

Abstract: The agronomic traits, including morphological and yield component traits, are important in barley breeding programs. In order to reveal the genetic foundation of agronomic traits of interest, in this study 122 doubled haploid lines from a cross between cultivars “Huaai 11” (six-rowed and dwarf) and “Huadamai 6” (two-rowed) were genotyped by 9680 SNPs and phenotyped 14 agronomic traits in 3 years, and the two datasets were used to conduct multi-locus genome-wide association studies. As a result, 913 quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 71 publications
(127 reference statements)
0
24
0
Order By: Relevance
“…Due to the stricter Bonferroni correction, the single-locus GWAS methods, including MLM and GLM, were not efficient to detect small effective loci of a complex trait (Wang et al, 2016). Recently, GWAS analysis in many species using the multi-locus methods showed significantly higher efficiency in the detection of small effective loci than the single-locus methods (Hu et al, 2018;Lü et al, 2018;Peng et al, 2018). Excluding the FASTmrEMMA, the four other multi-locus GWAS approaches, which ranged from 89 to 118 and ranged from 2 to 81, found more QTNs than the two single-locus methods ( Table 3).…”
Section: Comparison Of Gwas Methods By Single-locus and Multi-locusmentioning
confidence: 99%
“…Due to the stricter Bonferroni correction, the single-locus GWAS methods, including MLM and GLM, were not efficient to detect small effective loci of a complex trait (Wang et al, 2016). Recently, GWAS analysis in many species using the multi-locus methods showed significantly higher efficiency in the detection of small effective loci than the single-locus methods (Hu et al, 2018;Lü et al, 2018;Peng et al, 2018). Excluding the FASTmrEMMA, the four other multi-locus GWAS approaches, which ranged from 89 to 118 and ranged from 2 to 81, found more QTNs than the two single-locus methods ( Table 3).…”
Section: Comparison Of Gwas Methods By Single-locus and Multi-locusmentioning
confidence: 99%
“…These chromosomal regions represented 67, 90, and 80% of QTLs detected by the single-SNP, multi-SNP, and haplotype-based approaches, respectively, highlighting that the degree of colocalization with previously reported QTLs and genes was high for all three approaches. In a recent study on barley, Hu et al (2018) demonstrated that the use of multilocus models for main agronomic traits can detect more QTLs than traditional QTL analysis: among the 39 QTLs detected, 49% colocalized with same QTL regions in previous studies.…”
Section: Comparison With Candidate Genes and Qtlsmentioning
confidence: 97%
“…Several studies have also proved the potential of multilocus and haplotype-based models to identify known and novel associations with traits. In barley, Hu et al (2018) proved that among the QTLs detected by multilocus models, 51%, including some minor-effect QTLs, were novel. Moreover, Mihalyov et al (2017) explored the use of GWAS to characterize stem rust resistance genes in winter wheat and found that a multilocus model improved the identification of new loci with direct breeding applications.…”
Section: Comparison With Candidate Genes and Qtlsmentioning
confidence: 99%
See 1 more Smart Citation
“…SNPs detected by GBS have allowed the genetic dissection of genotypic variation in complex traits in many plant species [34][35][36]. Specifically, in oil palm the GBS technique has been used for identifying candidate genes related to oil bunch [37], bunch weight [20,37], stem height [21] and oil quality traits studies [38] with the enzymes ApeKI and PstI-MspI.…”
Section: Association Analysismentioning
confidence: 99%